Recent Developments in the Therapeutic Management of Diabetes Mellitus - Fraidoon Farzam; Aliseena Yussufpur (Penerbit Hellow Pustaka, 2026)
Diabetes mellitus (DM) represents a growing global health concern, imposing a substantial socio-economic burden on healthcare systems worldwide. Conventional therapeutic strategies have demonstrated limited success in addressing the multifactorial etiology of DM and are frequently associated with significant adverse effects. Consequently, there has been a surge in the development and evaluation of novel therapeutic modalities. This narrative review critically examines recent advancements in DM treatment and the associated implementation challenges. A comprehensive literature search was conducted using databases such as Web of Science, PubMed/MEDLINE, and Scopus, employing keywords including “diabetes mellitus,” “management of diabetes,” and “gene therapy.” Emerging evidence indicates considerable progress in DM management through innovative approaches such as nanotechnology-based drug delivery systems, gene therapy, stem cell therapy, medical nutrition therapy, and lifestyle interventions. Despite these advancements, several challenges persist, including the need for optimization of these therapies to achieve effective glycemic, lipid, and blood pressure control; enhancement of patient adherence to therapeutic regimens; safety and ethical considerations; and the development of efficient delivery systems. In conclusion, the integration of lifestyle modifications with pharmacological and emerging therapeutic strategies, along with their continued refinement, is essential for the establishment of safe, effective, and individualized clinical management protocols for diabetes mellitus.